Early Hypofractionated Salvage Radiotherapy for Post-Prostatectomy Biochemical Recurrence - Kruser, Tim J. (2010)
BACKGROUND: Post-prostatectomy adjuvant or salvage radiotherapy, when using standard fractionation, requires 6.5–8 weeks of treatment. We report on the safety and efficacy of an expedited radiotherapy course for salvage prostate radiotherapy. METHODS: A total of 108 consecutive patients were treated with salvage radiation therapy to 65 Gy in 26 fractions of 2.5 Gy. Median follow-up was 32.4 months. Median pre-salvage PSA was 0.44 (0.05–9.50). Eighteen patients (17%) received androgen deprivation following surgery or concurrently with radiation. RESULTS: The actuarial freedom from biochemical failure for the entire group at 4 years was 67% +/− 5.3%. An identical 67% control rate was seen at 5 years for the first 50 enrolled patients whose median followup was longer at 43 months. One acute grade 3 GU toxicity occurred, with no acute grade 3 GI and no late grade 3 toxicities observed. On univariate analysis, higher Gleason score (p=0.006), PSA doubling time ≤ 12 months (p=0.03), perineural invasion (p=0.06), and negative margins (p=0.06) showed association with unsuccessful salvage. On multivariate analysis, higher Gleason score (p=0.057) and negative margins (p=0.088) retained an association with biochemical failure. CONCLUSIONS: Hypofractionated radiotherapy (65 Gy in 2.5 Gy fractions in about 5 weeks) reduces the length of treatment by from 1–1/2 to 3 weeks relative to other treatment schedules commonly employed, produces low rates of loxicity, and demonstrates encouraging efficacy at 4 – 5 years. Hypofractionation may provide a convenient, resource efficient and well-tolerated salvage approach for the estimated 20–35,000 US men per year experiencing biochemical recurrence after prostatectomy.